Student engagement in university decision-making and governance : towards a more systemically inclusive student voice 2015 and 2016 : Good practice case studies report : Australian examples of student engagement. - Varnham, Sally; Olliffe, Bronwyn; Waite, Katrina; Cahill, Ann (Australia. Dept of Education and Training (DET), 2018)
Responses to our survey of student engagement practices in Australian universities (Varnham & ors 2017c), and stories volunteered to the project team at conferences, made it apparent that there were initiatives and existing practices at Australian universities that are already providing opportunity for students to have a significant representative role in decision making processes. Consequently, with the approval of the relevant institutions, we conducted interviews and focus groups with key personnel and students to gain an understanding of what these practices look like and how they are experienced by staff and students. Our aim was to create a body of exemplars that institutions keen to further develop their student engagement practices might draw on for ideas and implementation. Interviews and focus group sessions were audio-recorded and the recordings transcribed to provide a record of the practices explored at each institution. These transcripts were used to create the synopsis of each case study that is presented in this guide. This report is part of a set of four publications produced by Professor Varnham and her team that explore and promote the benefits of student engagement in university decision-making and governance. [Executive summary, ed]